Legal Protecton for Laborers with Non-Wage Rights After the Constitutional Court Decision Number 67/PUU-XI/2013 - et al., Ahmad Dwi Nuryanto (International Journal of Advanced Science and Technology, 2019)
The present study aims to find out the interpretation of definition and legal protection for other rights of laborers after the Court Constitution Decision Number 67/PUUXI/2013. The type of the present study is normative law with descritptive research. Secondary data were used for the analysis. They were collected by using literature study. The primary and secondary data were then quatitatively analyzed. The results indicate that, first, other rights of the laborers which were divided into: (a). Normative rights, that is, other rights given and regulated in Law of the Republic of Indonesia (e.g. severances, working tenure, rights changeable, and (b) other non-normative rights, meaning that it is given and regulated by related parties according to shared-agreement whether in Employment Agreement or Collective Labor Agreement. Second, legal protection for other rights of the laborers in Law of the Republic of Indonesia Number 67/PUU-XI/2013 had been present, but it did not yet fully implemented since the rights of non-wage for the laborers were excluded in payment by secured creditors.